Hepatitis C Genotype Influences Post-liver Transplant Outcomes. Issue 4 (April 2015) - Campos-Varela, Isabel; Lai, Jennifer C.; Verna, Elizabeth C.; O'Leary, Jacqueline G.; Todd Stravitz, R.; Forman, Lisa M.; Trotter, James F.; Brown, Robert S.; Terrault, Norah A.
<x xml:space="preserve">Abstract</x> Background In nontransplant patients with chronic hepatitis C virus (HCV), HCV genotype has been linked with a differential response to antiviral therapy, risk of steatosis and fibrosis, as well as all-cause mortality, but the role of HCV genotypes in posttransplant disease progression is less clear. Methods Using the multicenter CRUSH-C cohort, genotype-specific rates of advanced fibrosis, HCV-specific graft loss and response of antiviral therapy were examined. Results Among 745 recipients (605 [81%] genotype 1, 53 [7%] genotype 2, and 87 [12%] genotype 3), followed for a median of 3.1 years (range, 2.0–8.0), the unadjusted cumulative rate of advanced fibrosis at 3 years was 31%, 19%, and 19% for genotypes 1, 2, and 3 (P = 0.008). After multivariable adjustment, genotype remained a significant predictor, with genotype 2 having a 66% lower risk (P = 0.02) and genotype 3 having a 41% lower risk (P = 0.07) of advanced fibrosis compared to genotype 1 patients. The cumulative 5-year rates of HCV-specific graft survival were 84%, 90%, and 94% for genotypes 1, 2, and 3 (P = 0.10). A total of 37% received antiviral therapy, with higher rates of sustained virologic response in patients with genotype 2 (hazard ratios, 5.10; P = 0.003) and genotype 3 (hazard ratios, 3.27; P = 0.006) compared to patients with genotype 1. Conclusion Risk of advanced fibrosis and response to therapy are strongly influenced by genotype. Liver transplantation recipients with HCV genotype 1 have the highest risk of advanced fibrosis and lowest sustained virologic response rate. These findings highlight the need for genotype-specific management strategies.